Letter from the Presidents: Spring/Summer 2025 - Amanda Lickteig; Alan English (The Advocate, 2025)
Together, ATE-K Past-President Dr. Alan English and President Dr. Amanda Lickteig reflect on the recent spring conference, congratulate the newly-elected officers, and present readers with the spring/summer 2025 issue.
Keywords: Introductory letter; Letter from the Presidents; Spring/Summer 2025